Clinical experience with the Bicarbon heart valve prosthesis - Sakano Yasuhito; Kaminishi Yuichiro; Oki Shin-ichi; Konishi Hiroaki; Saito Tsutomu; Misawa Yoshio; Morita Hideki; Aizawa Kei (Journal of Cardiothoracic Surgery, 2007)
Abstract Bacground We have previously reported mid-term results of a study, which ended in January 2000, on the Bicarbon valve. The study concluded that the valve showed excellent clinical results, associated with a low incidence of valve-related complications. In the present study, the same patients were prospectively followed for an additional 5 years. Methods Forty-four patients had aortic valve replacement (AVR), 48 had mitral valve replacement (MVR), and 13 had both aortic and mitral valve replacement (DVR). The mean age of the 105 patients was 61.2 ± 11.3 years. The mean follow-up was 6.1 ± 1.9 years with a cumulative follow-up of 616 patient-years. Results There were 5 early deaths (4.7%: 4 in the AVR group and 1 in the MVR group) and 21 late deaths (3.4%/patient-year: 5 valve related deaths and 16 valve unrelated deaths). Survival at 8 years was 75.2 ± 7.0% in the AVR group, 76.6 ± 6.2% in the MVR group, and 55.4 ± 16.1% in the DVR group. The linearized incidence of thrombo-embolic complications, hemorrhagic complications, and paravalvular leaks in all patients was 0.65 ± 1.48%, 0.81 ± 1.69%, and 0.16 ± 0.54%/patient-year respectively. No other complications were observed. Conclusion The Bicarbon prosthetic heart valve has shown excellent long-term clinical results, associated with a low incidence of valve-related complications.